Thinking through Community Unionism - Cranford, Cynthia; Das Gupta, Tania; Ladd, Deena; Vosko, Leah F. (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
Case study based on multi-year ethnography of the efforts of a group of workers organizing with Toronto Organizing for Fair Employment (TOFFE), now the Workers' Action Centre of toronto, an active community partner in the Community University Research Alliance on Contingent Work. [The authors] attempt to conceptualize community unionism by locating the efforts of TOFFE in relation to two intersecting continua - a continuum of location that includes constitituency, site, and issue-based organizing, and a continuum of process, defined by hierarchical organizations at one pole, and particpatory organizations at the other pole. --From editor's introductory chapter, p. 39.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment